Power flow control of interlinked hybrid microgrids - Nutkani, Inam Ullah (2013)
Microgrids are small reliable grids formed by clustering distributed sources and loads together. They can, in principle, operate at different voltages and frequencies like 50 Hz, 60 Hz, 400 Hz or even dc. Tying them either to the mains grid or among themselves would certainly require some interlinking power converters, whose active and reactive power flow control should preferably be done autonomously without demanding communication links. This theme of investigation is now pursued, which upon performed appropriately, will result in more robust hybrid microgrids with many advantages like higher efficiency and lower reserve requirement. The theoretical findings concluded have already been verified through simulation and a scaled-down experimental system.